THEORETICAL BASIS OF STATE FINANCE RECEARCH IN THE SYSTEM OF SOCIAL PROTECTION - Borushok I. І. І. (The actual problems of regional economy development, 2019)
An important function of public finances is the creation of favorable conditions for the development of the domestic economy, raising the social standards of citizens and their social protection. Effective use of public finances helps to solve the problem of sustainable economic and social development of the state.The volatile external economic environment in the country, the crisis in the economy require in-depth study of the social protection system in the context of the public finances. The search of new mechanisms of the formation and management of public finances will ensure the dynamic development of Ukrainian economy, and its balance and rational use will lead to the formation of a favorable macroeconomic situation, which will contribute to the effective development of entrepreneurship, investment growth, as well as stability in the social protection and social security system.The theoretical approaches to financial support for social protection of the population in relation to the financial state potential and its impact on the socio-economic development of Ukraine are generalized.The author defines the essence of the state finances and social protection as a process that provides the unprotected sections of society with equal financial opportunities through fair distribution of financial resources and responsibility of the state. Measures to improve social protection while attracting the financial potential of the state are proposed.The analysis of the modern system of social protection of the population is conducted, the discrepancy between the volume of functions of the state and the volume of financial resources is determined, and the ways of eliminating these disparities are outlined. Keywords: public finances, social protection, social security, social sphere, financial potential of the state, financial resources, functions of public finances, financial mechanism.